Current penetration depth and effective conductivity of a nano-scale p-GaN/u-GaN alternating-layer p-type structure. (December 2018) - Yao, Yu-Feng; Chen, Hao-Tsung; Kuo, Yang; Su, Chia-Ying; Tu, Charng-Gan; Lin, Chun-Han; Kiang, Yean-Woei; Yang, Chih-Chung (C. C.)
Abstract: By combining the high mobility of a nm-scale u-GaN layer with the high hole concentration of the neighboring p-GaN layers for hole diffusing into the u-GaN layer, an extremely high effective conductivity in the lateral dimension can be obtained in a p-GaN/u-GaN alternating-layer structure. To better understand the current flow distribution and more accurately estimate the effective lateral conductivity and the current penetration depth, which is related to the vertical conductivity, in such a layered structure, we prepare a series of sample with different thickness combinations of the upper portion of a layered p-type structure to be characterized and the lower p-type portion of significantly higher conductivity. The measured sheet conductance results of the series of sample are fitted with a model, in which an exponential decay of conductance contribution with depth in the upper portion and a uniform distribution in the lower portion are assumed, to obtain the current penetration depth and effective conductivity of the upper portion. The relative size of the current penetration depth with respect to the total p-type layer thickness can be used as a criterion for high enough vertical conductivity in device application. Highlights: Demonstration of record-low resistivity in a p-type layer by forming a p-GaN/u-GaN alternating-layer nanostructure. Demonstration of a novel technique for more accurately measuring the current penetration depth and effective conductivity. Buildup of an effective model for simulating the conductivity of a nano-scale layered doped-semiconductor structure.